A quantitative method to determine osteogenic differentiation aptness of scaffold - Shilpa Trivedi; Kamini Srivastava; Anurag Gupta; Tajindra Singh Saluja; Sumit Kumar; Divya Mehrotra; Satyendra Kumar Singh (Elsevier, 2020)
Osteogenic differentiation of Mesenchymal stem cells (MSCs) on scaffold is crucial for bone tissue engineering. Alkaline phosphatase (ALP) assay is an important method of assessing osteogenesis. Here, a very simple and innovative procedure is being described for quantification of osteogenic differentiation of MSCs in presence of scaffold using ALP assay. Different concentrations of the scaffold particles with the same number of MSCs were assayed for alkaline phosphatase activity using p-NPP as substrate for ALP activity. G-bone scaffold was used in concentrations of 5, 20, 60 and 100 mg/ml and same number of MSCs were seeded. Any scaffold which can be grind and weighed may be used. It was found that100 mg/ml G-bone graft was most useful for promoting osteogenesis and addition of growth factors further promoted. So, we were able to ascertain the concentration of scaffold which promotes osteogenesis the most.